Optimizing Real-Time PCR methods for detection of ssaN gene Salmonella enterica subsp.enterica in the blood specimen - Oktania Sandra Puspita; Andi Yasmon; Beti Ernawati Dewi (Faculty of Medicine, Diponegoro University, 2020)
Background Typhoid fever caused by Salmonella typhi is a common acute infection of the reticuloendothelial system, intestinal lymphoid tissue, and gall bladder. Detection of Salmonella spp. is still based on cultures and serological methods.Widal test is one of the serological tests that is still widely used, especially in developing countries including Indonesia.Widal tests have low sensitivity and specificity. They often produce false positive or false negative results.ObjectiveThe aim of this study were i) real time PCR optimization to develop a Salmonella enterica detection system. ii) molecular detection of new target gene (ssaN gene) from blood specimens in typhoid fever patients.Methods An experimental laboratory study was performed from March to October 2016. Extraction of Salmonella typhi DNA is used as templates for the optimization of real time PCR reaction.The blood sample was from patients suspected with typhoid fever obtained from the Menteng Sub-district Health Center according to the inclusion criteria.ResultsSpecificity test of real time PCR showed that the primers and probes used are not cross-react against other microorganisms. Sensitivity test obtained minimal detection is at least 10 cfu/ml of blood specimen. In blood clinical specimens, real time PCR could detect 19 (38%) positive samples of 50 blood specimen from suspected typhoid fever patients. Eleven samples with negative Widal serology gives positive results in real time PCR.ConclusionReal time PCR used in this study can increase the level of rate of positive testing by 22% of the total specimens.Keywords : Salmonella enterica subsp.enterica, typhoid fever, ssaN gene, real time PCR